Towards the Hydrogen Economy in Paraguay: Green hydrogen production potential and end-uses. (15th August 2022) - Posso, Fausto; Galeano, Michel; Baranda, César; Franco, David; Rincón, Angel; Zambrano, Juan; Cavaliero, Carla; Lópes, Davi
Abstract: This study was conducted to estimate the potential for green H2 in Paraguay. A total production potential of 22.5 × 10 6 tons/year was obtained with a main contribution (93.34%) from solar photovoltaic. The greatest potential for producing H2 from solar and wind resources is in the Western region, and from hydro resources is in the Eastern region of the country. Two end-uses of green H2 were assessed: (1) automotive transportation, replacing gasoline and diesel; and (2) residential energy, replacing firewood and LPG for cooking in households across the country. In 16 of the 17 departments, green H2 is able to replace the overall consumption of gasoline and diesel, as well as firewood and LPG. Finally, energy service cost (mobility), environmental aspects and CO2 emissions were considered for three urban mobility technologies for the Metropolitan Area of Asunción. Results show that the mobility cost of fuel cell hybrid electric buses is still very high in comparison to diesel buses and battery electric buses. However, when a longer driving range is required, fuel cell hybrid electric buses could become a viable alternative in the long term. From an environmental point of view, green H2 used in fuel cell hybrid electric buses has the potential to save about 96% of CO2 emissions in comparison to diesel buses. It is concluded that the estimated green H2 production potential favors the incorporation of the Hydrogen Economy in Paraguay. Highlights: The estimated green H2 production potential in Paraguay is 22.5 × 10 6 tons/year. The H2 produced exceeds the demand of fuels in the selected sectors. In urban mobility, FCHEB buses have environmental advantages and economic disadvantages. An important reduction in GHG emissions could be achieved throughout green H2 use. The development of the Hydrogen Economy in Paraguay fosters its energy transition.